Pengaruh Ketimpangan Gender Terhadap Pertumbuhan Ekonomi: (Studi Pada Kabupaten/Kota di Nusa Tenggara Timur ) - Dyonisius H S Jewaru; Alfira Meilawijaya (Jurnal Statistika Terapan (ISSN 2807-6214), 2024)
This study aims to provide empirical evidence of whether gender inequality inhibits economic growth per capita in districts/cities in East Nusa Tenggara province (NTT). The data used in this study are secondary data from Statistics Indonesia-NTT consisting of annual data from 22 districts/cities in NTT for the period 2018-2022. Descriptive quadrant analysis and panel data regression with fixed effect models and robustness checks were carried out in the estimation of this research model. The results of this study indicate that gender inequality inhibits the growth of GRDP per capita in districts/cities in NTT Province. According to its aspects, gender equality in the aspects of work participation, education, and economy significantly drives the growth of Gross Regional Domestic Product per capita.